Delivering a geriatric OSCE station in times of Covid-19 using makeup artistry - Bauer, Daniel; Germano, Miria; Stierlin, Johanna; Brem, Beate; Stöckli, Yvette; Schnabel, Kai P. (GMS Journal for Medical Education, 2020)
In the wake of the Covid-19 pandemic, people over 65 or suffering from certain conditions were deemed at high risk and asked to isolate themselves. This led to the simulated patient (SP) program at the University of Bern being depleted of middle-aged and elderly SP. Meanwhile, an OSCE had to be delivered using adapted cases that minimized physical contact between candidates and SP. Short of suitable cases at such short notice, the case of an elderly patient with postural instability had to be added to the exam blueprint. With elderly SP off the roster, it was decided to use makeup effects to achieve visual authenticity. A combination of wigs (grey hair, hairdo), 3D Probondo transfers (forehead wrinkles), old age stipple (crow’s feet), and colouring (age spots) were used to achieve the old-age effects, while SPs wore scarves to cover their neckline. The lower face was covered with protective face masks in accordance with the exam’s Covid-19 hygiene protocol.Case-related feedback from candidates and examiners was analysed for any direct or indirect remark attributable to the ageing effects. As no comment touched upon the subject of the appearance of age, this was interpreted as success, as any distracting effect from the SPs’ appearance in this regard would surely have prompted remarks or even complaints. The SPs’ feedback revealed how applying the ageing effects helped them adopt the octogenarian’s role.This report explains how SP in their fifties were made fit for an octogenarian’s case in an OSCE using makeup effects. The effort required for the ageing simulation was considerable, but it is hoped that in future, with more planning time, the amount of effort required can be reduced. The feedback obtained from the candidates suggest the appearance of SPs was not experienced as a distraction, which was the primary objective of this exercise. Adapting our approach to their own contexts allows educators to include cases with elderly patients in their OSCE that cannot be re-written for younger SP, so long as Covid-19 prevents elderly SP from participating.